KARAKTERISTIK BATUBARA TERPENGARUH INTRUSI DI TAMBANG AIR LAYA, SUMATRA SELATAN DAN POTENSINYA SEBAGAI MATERIAL UNTUK PEMBUATAN GRAFIT SINTETIS: THE CHARACTERISTICS OF HEAT-AFFECTED COAL IN AIR LAYA MINE, SOUTH SUMATRA AND ITS POTENTIAL AS AN ALTERNATIVE SOURCE OF SYNTHETIC GRAPHITE - Arsha Maulana; Ferian Anggara (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2020)
Graphite can be applied in various uses for example as a heat resistant materials, batteries, and electrodes. Graphite material can be obtained from synthetic graphite which produced from anthracite coal that is heated at 2000ÂºC or above. Naturally heat affected coal can be found in Tambang Air Laya (TAL), Tanjung Enim, South Sumatra where the coal is affected by the presence of igneous intrusion. According to these conditions, it is important to conduct the research to determine the characteristics of heat affected coal and its potential as an alternative source of synthetic graphite. Four samples of heat affected coal obtained from four seams with varying distances to the body of igneous intrusion are prepared for several analyses, namely petrographic, random vitrinite reflectance (Rvr), proximate, X-Ray Diffractometry (XRD), Total Carbon (TC), Total Organic Carbon (TOC), and Total Inorganic Carbon (TIC), as well as micro-Raman spectroscopy. The heat affected coal shows the tendency of increasing vitrinite reflectance and fixed carbon content and decreasing moisture and volatile matter towards the igneous intrusion body. The heat affected coal (A1 Coal) with the closest distance to the igneous intrusion body has the highest rank (low volatile bituminous coal; %Ro= 2,01%) and mineral percentage. A1 Coal is associated with mineral lempung such as illite, smectite, and rektorit that can increase the degree of crystalinity in the process of coalification and that would catalyze the formation of synthetic graphite in the next process.